Anti-proliferative effects of calcitriol on endothelial cells derived from two different microenvironments - Chung, I.; Yu, W.D.; Karpf, A.R.; Flynn, G.; Bernardi, R.J.; Modzelewski, R.A.; Johnson, C.S.; Trump, D.L. (2007)
Calcitriol (1,25-dihydroxycholecalciferol), the active form of Vitamin D, is anti-proliferative in tumor cells and tumor-derived endothelial cells (TDEC). However, endothelial cells isolated from normal tissues as cell lines or freshly isolated cells or from implanted Matrigel plugs (MDEC) are relatively resistant. Both TDEC and. MDEC express similar amounts of Vitamin D receptor (VDR) protein. Although the VDR from TDEC has higher binding affinity for calcitriol than those from MDEC, VDR in both cell types translocates to the nucleus and transactivates the 24-hydroxylase promoter-luciferase construct. Calcitriol selectively inhibits the growth of TDEC but not MDEC by inducing G(0)/G(1) cell cycle arrest and by promoting apoptosis. This selectivity appears to be related to 24-hydroxylase (CYP24) expression. Calcitriol significantly induced CYP24 expression in MDEC but not in TDEC and inhibition of CYP24 activity in MDEC restores their sensitivity to calcitriol. These findings indicate that the induction of CYP24 expression differs in endothelial cells isolated from different microenvironments (TDEC versus MDEC) and that this distinction contributes to selective calcitriol-mediated growth inhibition in these cell types. (c) 2006 Elsevier Ltd. All rights reserved.